Enhancing employee performance through motivation: the mediating roles of green work environments and engagement in Jakarta’s logistics sector - Nusraningrum, Dewi; Rahmawati, Aisyah; Wider, Walton; Jiang, Leilei; Udang, Lester Naces (Frontiers in Sociology, 2024)
This study aims to analyze the mediating role of employee engagement and the green work environment in the relationship between motivation and the performance of logistics company employees in Jakarta, Indonesia. Employing a causal quantitative research approach, we distributed 222 questionnaires among logistics employees from four surrounding cities in Jakarta, namely Bogor, Depok, Tangerang, and Bekasi. These questionnaires were adapted from past studies. The data were processed using Structural Equation Modeling (SEM) with Partial Least Squares. The results showed that employee performance in logistics companies was positively and significantly influenced by motivation. Furthermore, a green work environment and employee engagement were found to significantly mediate the relationship between motivation and performance. These findings underscore the importance of a green work environment and employee engagement in enhancing motivation and performance in logistics companies. The study implies that employee performance in logistics companies can be elevated through the provision of a green work environment, alongside fostering employee motivation and engagement.